CHOA Concussion Consensus: Establishing a Uniform Policy for Academic Accommodations. (March 2014) - Popoli, David Michael; Burns, Thomas G.; Meehan, William P.; Reisner, Andrew
Concussion research generally centers on physical challenges, though aspects such as social functioning and returning to school also warrant attention in pediatric populations. Restoring academic performance postconcussion remains a challenge. Here we provide recommendations addressing a uniform policy for pediatric concussion patients in academic institutions. Tools that may minimize difficulty with academic re-entry include independent educational evaluations, individualized educational programs (IEPs), student support teams (SSTs), letters of academic accommodation, time off, and 504 Plans. Recognition and treatment is crucial for symptom relief and prevention of functional disruption, as is specialist referral during the acute window. We recommend early intervention with a letter of academic accommodation and SST and suggest that 504 Plans and IEPs be reserved for protracted or medically complicated cases. Students with concussion should be observed for anxiety and depression because these symptoms can lead to prolonged recovery, decreased quality of life, and other social challenges.